2017
DOI: 10.3389/fimmu.2017.00646
|View full text |Cite
|
Sign up to set email alerts
|

Fc-Galactosylation of Human Immunoglobulin Gamma Isotypes Improves C1q Binding and Enhances Complement-Dependent Cytotoxicity

Abstract: Binding of the complement component C1q to the CH2 domain of antigen-bound immunoglobulin gamma (IgG) activates the classical complement pathway and depends on its close proximity to Fc fragments of neighboring antibodies. IgG subclasses contain a highly conserved asparagine 297 (N)-linked biantennary glycan within their CH2 domains, the core structure of which can be extended with terminal galactose and sialic acid residues. To investigate whether Fc-glycosylation regulates effector functions of human IgG sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
154
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(161 citation statements)
references
References 40 publications
7
154
0
Order By: Relevance
“…Deficiency of core fucose on the Fc portion of IgG results in a dramatic increase in antibody‐dependent cell‐mediated cytotoxicity, which is important in antibody treatment of patients with T‐cell leukemia . In contrast, increased galactosylation on the Fc portion of IgG enhances complement‐dependent cytotoxicity . High‐dose intravenous IgG therapy is commonly used for autoimmune diseases with unknown etiology.…”
Section: Glyco‐therapy Opens Up a New Field Of Medical Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of core fucose on the Fc portion of IgG results in a dramatic increase in antibody‐dependent cell‐mediated cytotoxicity, which is important in antibody treatment of patients with T‐cell leukemia . In contrast, increased galactosylation on the Fc portion of IgG enhances complement‐dependent cytotoxicity . High‐dose intravenous IgG therapy is commonly used for autoimmune diseases with unknown etiology.…”
Section: Glyco‐therapy Opens Up a New Field Of Medical Sciencementioning
confidence: 99%
“…57 In contrast, increased galactosylation on the Fc portion of IgG enhances complement-dependent cytotoxicity. 58 High-dose intravenous IgG therapy is commonly used for autoimmune diseases with unknown etiology. Antibody therapy using IgG devoid of N-glycans has been used clinically, but its effect varies from case to case.…”
Section: Glyco-therapy Opens Up a New Field Of Medical Sciencementioning
confidence: 99%
“…Similarly, the G1 glycoform of Rituximab triggered a CDC response twice as large as that triggered by the G0 glycoform (Jefferis, ). Nevertheless, the CDC improved efficacy is restricted to IgG1 and IgG3 subclasses, which suggests that Fc‐galactosylation alone is not sufficient for IgG2 and IgG4 to promote CDC activity (Peschke et al, ). Interestingly, recent reports revealed that Fc galactosylation induces a positive impact on the binding affinity of IgG1 to FcγRIIa and IIIa receptors and ADCC activity (Subedi & Barb, ; Thomann et al, ; Thomann, Reckermann, Reusch, Prasser, & Tejada, ).…”
Section: Antibody Glycoengineering Strategiesmentioning
confidence: 99%
“…A representative glycan profile from IgG1 expressed in CHO‐K1 cells using MALDI‐TOF mass spectrometry analysis is presented in Figure (Chung, Wang, Yang, Yin, et al, ). Specific glycoforms on a rMAb can have significant effects on the drug's bioactivities and therapeutic properties, such as high‐mannose glycans can increase antibody clearance rates (Yu et al, ), afucosylation, bisecting GlcNAc residues, and high‐mannose glycans can enhance ADCC activity (Jefferis, ; Shi & Goudar, ; Zhong et al, ) and galactosylation can improve CDC activity (Liu, ; Peschke, Keller, Weber, Quast, & Lünemann, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, IgGs lacking core fucosylation exhibit increased affinity for FcγRIIIA and are therefore significantly more potent in eliciting antibody-dependent cellular cytotoxicity 17,18 . Furthermore, the degree of galactosylation of the Fc glycan influences an IgGs ability to activate the complement system 19 . Consequently, IgG antibodies lacking the Fc glycan fail to bind to most Fc receptors and are unable to activate the complement system 20,21 .…”
Section: Introductionmentioning
confidence: 99%